Follow‐up of the melanoma patient. Issue 2 (12th December 2018) - Deschner, Benjamin; Wayne, Jeffrey D.
Abstract : Follow‐up of the melanoma patient involves many different methods of surveillance. Specific guidelines for modalities and frequency are flexible and largely open to physician preference. Patient education and self‐examination are generally viewed as crucial and cost‐effective for recurrence detection. Increased frequency of clinical follow‐up, laboratory studies, and imaging has not demonstrated survival benefit in surveillance. However, appropriate application of these different methods is controversial and evolving, especially with changing surgical management and new medical therapies.